Supplement to the manuscript "Mapping Arctic Lake Ice Backscatter Anomalies using Sentinel-1 Time Series on Google Earth Engine" submitted to "Remote Sensing" - Georg, Pointner; Annett, Bartsch (Zenodo, 2021)
Geospatial raster data and vector data created in the frame of the study "Mapping Arctic Lake Ice Backscatter Anomalies using Sentinel-1 Time Series on Google Earth Engine" submitted to the journal "Remote Sensing" and Python code to reproduce the results. Restricted version for peer review only. The dataset will be made openly available upon the acceptance of the manuscript. : The creation of this dataset was supported by the European Union's HORIZON2020 research projects Nunataryuk [grant number 773421] and CHARTER [grant number 869471], and the doctoral college DK GIScience at the University of Salzburg [Austrian Science Fund (FWF) project number W 1237].